Public health, trade unions and empowerment: From learning to draft resolutions to addressing the socioeconomic determinants of health - Jane Thomas; Sean Tunney; Adam Cox (Social Theory & Health, 2026)
Abstract Community empowerment projects aimed at improving health and wellbeing have tended to be ‘place-based’. But they may also be based on ‘communities of interest’. This paper advances an original conception of health-related empowerment by focusing on the work of trade unions, which we treat as being among such communities. Organised labour improves health and reduces inequalities through processes including collective bargaining, even as public health actors have shown resistance to engaging with unions. We focus on an unresearched area of unions’ andragogy that is central to empowerment: that of motion writing and resolution-related mobilisation, arguing this has direct and underexploited implications for public health. Drawing on triangulated data from a UK-wide survey of unions representing more than 2 million members, in-depth interviews and website analysis, we consider how resolution-associated practices can form bridges between people’s individual concerns and collective decision-making. Such ‘micro-meso-macro’ connections can support initiatives that other empowerment projects have failed to establish. This generates a new resolutions-based conceptual model: the multi-level empowerment pathway. Our research contests the prevailing public health paradigm. We build on previous union–health research to help reconsider action on health determinants operating as global challenges, suggesting an internationally applicable infrastructure for participatory action.